2012
DOI: 10.1128/aac.06102-11
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ceftobiprole Medocaril against Enterococcus faecalis in a Murine Urinary Tract Infection Model

Abstract: We evaluated ceftobiprole against the well-characterized Enterococcus faecalis strain OG1RF (with and without the ␤-lactamase [Bla] plasmid pBEM10) in a murine urinary tract infection (UTI) model. Ceftobiprole was equally effective for Bla ؉ and Bla ؊ OG1 strains, while ampicillin was moderately to markedly (depending on the inoculum) less effective against Bla ؉ than Bla ؊ OG1 strains. These data illustrate an in vivo effect on ampicillin of Bla production by E. faecalis and the stability and efficacy of ceft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The authors observed 5log bacterial reductions in high concentration (50 mg/kg) of β -lactam derivatives. This reduction was very significant in animal models when compared with the earlier reports, where ampicillin (50 mg/kg) was used in the same infectious model [ 45 ]. The reduction by compound 3 in intravenous model was observed to be better than daptomycin in intravenous model reported earlier [ 46 ].…”
Section: Discussionmentioning
confidence: 82%
“…The authors observed 5log bacterial reductions in high concentration (50 mg/kg) of β -lactam derivatives. This reduction was very significant in animal models when compared with the earlier reports, where ampicillin (50 mg/kg) was used in the same infectious model [ 45 ]. The reduction by compound 3 in intravenous model was observed to be better than daptomycin in intravenous model reported earlier [ 46 ].…”
Section: Discussionmentioning
confidence: 82%
“…It is possible that CspR may be one of the 'moonlighting' protein group, meaning that it can have two unrelated functions according to its intra-or extracellular location. To date, for the prevention of E. faecalis infections, in addition to lipoteichoic acid and capsular polysaccharides, three proteins known as virulence factors have been proposed as possible immunotherapy targets: the general stress protein Gls24, the collagen adhesion Ace, and the endocarditis-and biofilm-associated pilus Ebp (Giard et al, 2000;Huebner et al, 2000;Lebreton et al, 2009;Murray, 1990;Singh & Murray, 2012;Singh et al, 2007;Teng et al, 2005). Our results showed that a cold-shock RNA-binding protein can present a double localization, both intercellularly and at the surface of the bacteria, and that anti-CspR antibody protects insect larvae against infection by E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…Food and water were allowed ad libitum. Literature was used to design in-house pharmacokinetic studies [58][59][60] and results from those studies were used to select dosing concentrations and intervals for the present study in which amp and cipro were given twice daily at 8-h intervals and fosfo was given once daily for three consecutive days. Fecal samples were collected at euthanasia from the distal ileum and proximal colon after 24 h (1 day), 48 h (2 days) and 72 h (3 days) of treatment.…”
Section: Animal Model and Antibiotic Exposurementioning
confidence: 99%